32 Does complete revascularisation confers a long term survival benefit in patients with chronically occluded coronary vessels?. (9th June 2011) - Shah, N H; Khan, M F; Ungvari, T; Loh, P H; Buchanan, L; Hoye, A; Oliver, R M; Thackray, S; Caplin, J L; Alamgir, M F
Abstract : Introduction: Chronic total occlusion (CTO) of coronary vessels is a relatively common finding on diagnostic angiography. There has been increasing interest in this clinically important area with development of technologies resulting in improved recanalisation rates. However, long term survival data in this cohort is lacking. In this study we looked at survival of patients in whom complete, successful revascularisation was achieved. Methods: We identified consecutive patients, found to have CTO of at least one vessel of more than 1-month duration, on angiography performed between January 1999 and August 2000 in a single tertiary centre. We used a dedicated database to record data on variables and used central National Health Service database to obtain survival data. Results were analysed using SPSS statistics version 17. Results: We included 331 patients in the analysis. Mean age was 56.8 ±19.8 years, 76.1% were male and 21.8% (n=71) were diabetic. Mean duration of CTO was 29.5±25.9 months and was only reliably estimated in 82.5% of cases. Median follow-up duration was 10.09±3.3 years. Complete revascularisation was successfully achieved in 53.5% (n=177) patients, while 46.5% (n=154) were either treated medically from the outset or had failed or incomplete revascularisation. Both groups were age matched. Overall 10-year survival was 66.5%; those with complete revascularisation had significantly improved survival over those with incomplete revascularisation or medical therapy (75.1% vs 56.5%, p<0.001). Conclusion: Complete revascularisation confers a significant long term survival in patients with CTO and underscores the importance of improved recanalisation rates when performing angioplasty in this patient group. Overall survival was relatively poor and emphasises the importance of optimal medical therapy in this cohort.